1992
DOI: 10.1139/v92-336
|View full text |Cite
|
Sign up to set email alerts
|

The acidic specific capsular polysaccharide of Rhodococcusequi serotype 3. Structural elucidation and stereochemical analysis of the lactate ether and pyruvate acetal substituents

Abstract: . Can. J . Chem. 70, 2664 (1992). The specific capsular polysaccharide produced by Rhodococcus equi serotype 3 was found to be a high-molecularweight acidic polymer composed of D-glucose, D-galactose, D-glucuronic acid, 4-0-[(S)-1-carboxyethyll-D-mannose, and pyruvic acid in equal molar proportions. Structural analysis, employing a combination of chemical and nuclear magnetic resonance techniques, established that the polysaccharide is composed of linear repeating tetrasaccharide units, in which (R)-1-carboxye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Pyruvic acid was detected in the hydrolysate of SM-1 EPS obtained with 2% TFA, and its content was calculated to be 10.3% (W/W). [17][18][19][20][21] They noted the presence of pyruvic acid in its acetal form in EPS of serotypes 1, 3, 4, and 7, but they did not mention the presence of fatty acids.…”
Section: Physicochemical Properties Of Sm-1 Epsmentioning
confidence: 99%
“…Pyruvic acid was detected in the hydrolysate of SM-1 EPS obtained with 2% TFA, and its content was calculated to be 10.3% (W/W). [17][18][19][20][21] They noted the presence of pyruvic acid in its acetal form in EPS of serotypes 1, 3, 4, and 7, but they did not mention the presence of fatty acids.…”
Section: Physicochemical Properties Of Sm-1 Epsmentioning
confidence: 99%
“…It was shown that EPS of pathogenic Rhodococcus equi 1,2 play a major role in the virulence of this zoonic pathogen, a cause of equine necrotizing pneumonia. The EPS structures of the five capsule-based serotypes of R. equi have been fully characterized [3][4][5][6][7] and have provided structural information assisting in the determination of their role in virulence, in diagnostic serology, and in their use as investigative conjugate vaccines. Secondly, EPS was demonstrated to play a role in the bacterial degradation of non-polar aromatic and aliphatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…A few of the polysaccharides are known to associate with lactic acids, all of which are linked to sugar residues through ether link ages. 13,14) The desulfated Gymnodinium A3 polysaccharide exhibit ed a1H NMR signal at 6 1.33 (d, J=6.8 Hz) which was as signable to the signal of the methyl doublet of lactate moie ty (Fig. 6).13,28) This signal disappeared after deacylation.…”
Section: Resultsmentioning
confidence: 89%